Development of new attachment solution for patient transfer device - Birgersson, Hanna; Sjöberg, Deborah (My University, 2026)
Patient handling is a common task in healthcare associated with physical strain and risk of work-related injuries. Assistive devices for patient transfer have there fore become important tools for improving working conditions and reducing manual handling. Atle® 180, developed by Njord Medtech, is a patient transfer device de signed to perform lateral transfers by sliding patients between surfaces. However, the current attachment solution presents challenges related to usability, time effi ciency and risk of detachment during use. The aim of this project was to explore, develop and evaluate concepts for the attach ment solution in Atle® 180. The focus of the work was on developing a solution that is easier to attach, more secure and time-efficient during use. The project followed an iterative product development process consisting of six main phases: Pre-study, User research, Problem analysis, Ideation, Evaluation and Development. User needs and contextual constraints were identified through a literature study, observations and interviews with healthcare workers at Sahlgrenska University Hospital. Identi fied needs were translated into design guidelines and requirements that formed the basis for the concept development and evaluation. Several concepts were developed iteratively using structured ideation methods, and evaluated through mockups and Pugh matrix evaluation. The selected concept was further refined through CAD modelling, prototyping and ergonomic validation. The final design solution presents an alternative attachment solution intended to reduce handling problems while maintaining functionality and compatibility with Atle®. The project has shown how an iterative development approach can support im provements in the attachment system of a patient transfer device by addressing both technical performance and user needs in healthcare environment
Keywords: product development; patient transfer; prototyping; industrial design; concept evaluation; patient transfer device